Successful treatment of a 15 years-old obese adolescent patient with botulinum anti-toxin after gastric Botox and systemic botulism findings: a case report - Muhammed Furkan Yücer; Alper Kaçar; Hüseyin Dağ; Ahmet İrdem (Iberoamerican Journal of Medicine, 2023)
Obesity is an increasingly common public health problem in children. The main goal in the fight against obesity is to prevent the development of obesity by healthy eating, increasing physical activity and reducing screen time. Patients with obesity should be treated in a multidisciplinary manner in accordance with the guidelines. In children and adolescents, applications such as gastric Botox, which are not included in the guidelines and for which there is insufficient literature information, should be avoided. Obese patients with Botulism side effects should be questioned about this application and Botulism antitoxin should be administered in appropriate cases. In this case report, we present a 15-year-old adolescent girl who developed botulism after gastric Botox administration in another medical institution and was successfully treated with Botulism antitoxin and prostigmine.